2018
DOI: 10.1016/j.dib.2018.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence data and analysis of type strains ‘Pusillimonas nitritireducens’ and ‘Pusillimonas subterraneus’ isolated from nitrate- and radionuclide-contaminated groundwater in Russia

Abstract: Two strains, ‘Pusillimonas nitritireducens’ JR1/69-2-13T and ‘Pusillimonas subterraneus’ JR1/69-3-13T, of aerobic, motile, Gram-negative, non-spore-forming, organotrophic, psychrotolerant bacteria were isolated from a sample of nitrate- and radionuclide-contaminated groundwater in Russia. Here we describe the draft genomes of these strains. The sequenced and annotated genome of the strain JR1/69-2-13T contained 4.3 Mbp with 4108 protein-coding genes. The genome of the strain JR1/69-3-13T contained 4.5 Mbp with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thus, analysis of genomes of the strains JR1/69-2-13 and JR1/69-3-13 testifies to their belonging to two novel species within the Pusillimonas genus with proposed names 'Pusillimonas nitritireducens' and 'Pusillimonas subterraneus', respectively [42]. The genome sequences of both strains provide an insight into the genomic basis of their resistance to heavy metals and metalloid and ability to survive in nitrate-contaminated groundwater.…”
Section: Metabolic Potential Of Pusillimonas and Roseomonas Strains mentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, analysis of genomes of the strains JR1/69-2-13 and JR1/69-3-13 testifies to their belonging to two novel species within the Pusillimonas genus with proposed names 'Pusillimonas nitritireducens' and 'Pusillimonas subterraneus', respectively [42]. The genome sequences of both strains provide an insight into the genomic basis of their resistance to heavy metals and metalloid and ability to survive in nitrate-contaminated groundwater.…”
Section: Metabolic Potential Of Pusillimonas and Roseomonas Strains mentioning
confidence: 94%
“…Our previous study [42] demonstrated that average nucleotide identity (ANI) values of JR1/69-2-13 and JR1/69-3-13 genomes with genomes of Pusillimonas strains were within the range of 77.6%-84.5%. These ANI values were below the species border, proposed to be 95%-96% [51].…”
Section: Metabolic Potential Of Pusillimonas and Roseomonas Strains mentioning
confidence: 98%
See 2 more Smart Citations
“…Halomonas has also been shown to contribute to the denitrifying process in an expanded granular sludge bioreactor(Miao et al 2018). Meanwhile, Pusillimonas was isolated from nitrate and radionuclide-contaminated groundwater, and shown to possess denitrifying functional genes(Grouzdev et al, 2018). Truepera has been reported as one of the denitri ers in a sequencing batch bio lm reactor used for land ll leachate treatment(Yin et al 2018), and exhibited a high dominance of over 20% in a similar denitri cation sequencing batch reactor(Shi et al, 2022).…”
mentioning
confidence: 99%